ACTIVITIES OF DRUGS LOGISTIC AT PT KIMIA FARMA APOTEK BUSINESS UNIT PALU - Simatupang, Ferdi Samuel; Sulaeman Miru; Syamsuddin (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This study aims to analyze business problems of PT Kimia Farma Apotek Business Unit Palu. There are several issues in the community, including the absence of certain brands of drugs sought by the people and the price of drugs that are quite expensive compared to other private pharmacies. This research describes inbound activities, conversion operations, and outbound logistics at PT Kimia Farma Apotek Business Unit Palu. The type of research used was descriptive, using a qualitative approach. The types of data used were primary and secondary data. The data were collected through interviews. The results of this study indicate that in inbound logistics activities, there are obstacles in the process of fulfilling drugs, some of which are pharmacies having difficulty fulfilling a drug of a certain brand if it has not been registered (listing) at the Head Office of PT Kimia Farma Apotek, this happens because the company makes rules centrally so that the Business Unit cannot decide our of its authority. Conversion operation logistics activities are very good because this activity is carried out to maintain the quality of drugs, and the amount is kept at the minimum and maximum limits. Outbound logistics activities are good, namely sales to individuals/community and cooperation with agencies, except that sales to individuals/the community should be considered so that the socialization of the